1974
DOI: 10.1063/1.1681320
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectra and characterization of the products of fluorine atom reactions with matrix isolated NO molecules

Abstract: Simultaneous matrix deposition of F2 and NO molecules at high dilution in argon and nitrogen onto an 8°K CsI window produces three new infrared absorptions in addition to those of normal, FN-bonded nitrosyl fluoride, FNO. The infrared features at 1886.6, 734.9, and 492.2 cm−1 (Ar matrix) and their 15N and 18O isotopic counterparts were assigned to the previously unobserved FO-bonded isomer NOF, which appears to be a bent molecule having a molecular geometry similar to that of nitrosyl fluoride. Controlled fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The single-crystal X-ray analysis revealed that NO bound to the MOF metal nodes were crystallographically S13). [70][71][72] Spectroscopic analysis using DRIFTS revealed a 78 cm À 1 -shift in the NÀ O stretching frequency to 1798 cm À 1 upon metal coordination in Co 2 (DOBDC) compared to that of non-coordinated NO (1876 cm À 1 ), [73] that is in line with literature reports monitoring NO coordination in cobaltbased organometallic complexes and in an isostructural MOF, Fe 2 (DOBDC). [36,70] DRIFTS studies were used for investigating NO@Co 2 (DOBDC) for the first time (Figure 8) to demonstrate that NO coordinated to the metal centers can be efficiently released and replaced with water molecules.…”
Section: Methodssupporting
confidence: 89%
“…The single-crystal X-ray analysis revealed that NO bound to the MOF metal nodes were crystallographically S13). [70][71][72] Spectroscopic analysis using DRIFTS revealed a 78 cm À 1 -shift in the NÀ O stretching frequency to 1798 cm À 1 upon metal coordination in Co 2 (DOBDC) compared to that of non-coordinated NO (1876 cm À 1 ), [73] that is in line with literature reports monitoring NO coordination in cobaltbased organometallic complexes and in an isostructural MOF, Fe 2 (DOBDC). [36,70] DRIFTS studies were used for investigating NO@Co 2 (DOBDC) for the first time (Figure 8) to demonstrate that NO coordinated to the metal centers can be efficiently released and replaced with water molecules.…”
Section: Methodssupporting
confidence: 89%
“…It shows a set of four lines due to NO molecules stabilised in different local sites of the matrix: 1877, 1872, 1867 and 1862 cm -1 , and two relatively weak lines due to NO dimers: 14 1863 and 1776 cm -1 . Also shown are the spectral lines of products that are formed upon condensation of the gases: FNO at 1849.6, 751 and 509.8 cm -1 , and its isomer ONF 5 at 1884 and 735 cm -1 . Photolysis at 16 K leads to a small increase in the FNO lines and a decrease in the intensity of the NO lines.…”
Section: H/mtmentioning
confidence: 99%
“…[1][2][3] However, experimental data concerning this radical are virtually nonexistent, and this makes it difficult to evaluate the accuracy of the calculations or even to choose an appropriate computational method for calculating the properties of the radical.The F 2 NO radical is an intermediate species in the reaction of fluorine atoms with nitric oxide:Although this scheme was used successfully to synthesise F 3 NO, 4 attempts to detect the intermediate F 2 NO in mixtures of F 2 and NO in the gas phase and in solids were completely unsuccessful. 4,5 In this communication, we describe a method which permits the stabilization of F 2 NO radicals formed in reaction (2). We present, for the first time, the infrared absorption spectra and EPR spectra of this radical isolated in a rare gas matrix.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…F + NO. In studies of the infrared spectra of the products of the photolysis of F 2 in argon or nitrogen matrices to which a small concentration of NO had been added, Smardzewski and Fox [29][30][31] observed very prominent absorptions of FNO. In addition, less prominent absorptions which appeared within about 35 cm -I of each of the three FNO fundamentals were assigned to the previously undetected FON isomer, for which a potential minimum had been found in the ab initio calculations of Peslak and co-workers [32].…”
Section: Types Of F-atom Reactionmentioning
confidence: 99%